Electricity: Principles and Applications - J. Fowler Richard (Mc Graw Hill, 2003)
This textbook is written for students just beginning their study of electricity. No previous formal training in the subject is assumed. Only arithmetic and basic algedbra are used in explaining and solving most electrical problems. Although simultaneous equations are introduced in Chap. 6, they are defined and explained in some detail before actually being used. Similarly, the elements of trigonometry that relate to ac circuits are fully explained as needed.